Multiple Sessions of Antimicrobial Photodynamic Therapy Improve Periodontal Outcomes in Patients with Down Syndrome: A 12-Month Randomized Clinical Trial - Rafael Ferreira; Sebastião Luiz Aguiar Greghi; Adriana Campos Passanezi Sant’Ana; Mariana Schutzer Ragghianti Zangrando; Carla Andreotti Damante (Dentistry Journal)
Background/Objectives: Individuals with Down syndrome (DS) often present with severe periodontal disease at a young age. Adjuvant treatments to scaling and root planing (SRP), such as antimicrobial photodynamic therapy (aPDT), may benefit this population. This study evaluated the effectiveness of aPDT as an adjunct to SRP in individuals with DS. A randomized, double-blind, parallel trial was conducted with 37 individuals with DS. Methods: The test group (aPDT; n = 18) received SRP + aPDT, while the control group (C group; n = 19) received SRP only. For aPDT, a red laser (658 nm; 0.1 W; 2229 J/cm2; 40 s sweeping with optical fiber) combined with methylene blue (MB) (100 µg/mL) was applied across repeated sessions (on days 3, 7, and 14). Clinical parameters, such as plaque index (PI), clinical attachment level (CAL), probing depth (PD), and bleeding on probing (BOP), were recorded at baseline and after 3, 6, and 12 months of treatment. Statistical analyses were performed using parametric and non-parametric tests (p < 0.05). Results: Both treatments promoted improvements in all clinical periodontal parameters (p < 0.05). The aPDT group showed a statistically significant reduction in CAL at 3 months (aPDT = 4.58 mm vs. C = 4.72 mm; p < 0.05) and 12 months (aPDT = 4.59 mm vs. C = 4.84 mm; p < 0.05). Conclusions: aPDT improved periodontal health in the long term through a stable gain in attachment.